Study on the Friction Torque Calculation and Experimentation of Cycloid Ball Planetary Transmission - Zhu Jiangtao (Jixie chuandong)
Based on the kinematics of cycloid steel ball planetary transmission,the contact state between the meshing pair and the speed reducer is determined. The mathematical model of the friction torque of the gear pair and the constant velocity pair is established. The friction torque is compared and analyzed. The influence of different parameters on the friction torque of the gear pair is studied,and the variation law of friction torque of the prototype under different axial force is tested. The results show that the meshing point of the gear pair has a macro sliding condition,and there is no sliding condition in the meshing point. The friction torque of the gear pair is much larger than that of the constant speed meshing pair. Therefore,the friction torque can be replaced by the friction torque of the gear pair. Influence of axial force and the radius of the friction torque is larger,and the load has little influence on the friction torque. The experimental results are in good agreement with the theoretical results,which proves the correctness of the theoretical model.